Juventudes em cena no cotidiano escolar : movimentos de (re)produção de silenciamentos, regulações de gênero, subversões e resistências - Nascimento, Ana Paula Leite (2019)
The thesis aimed to analyze the movement of (re) production of silence, invisibility and gender regulations; and, the (re) production of visibilities, subversions and resistances of youngsters at the Sergipe Federal Institute of Education, Science, and Technology (IFS) daily life. In the contextualization and problematization of the corpus, some theoretical-analytical categories were prioritized in the process of successive approximations in order to capture certain determinations that constitute the totality of the questioned object. In this sense, we hold discussions on youth, its conceptual elements as well as material and social conditions of existence; school daily life, cultures, identity markers, individualities and juvenile subjectivities; social constructions of gender and professional choices; regulation of gender and subversion of corporalities and sexualities; and, marks of disciplinary power and resistance in school context. This is a qualitative research which was constituted by a case study through macro and micro reality data. This study was based on dialectical historical materialism, feminist and gender theories. The research universe encompassed students enrolled in IFS campuses in Integrated Secondary Education and Subsequent Technical Education modalities to characterize the population profile, and also students enrolled in the Integrated High School from Lagarto and Aracaju campuses that constituted the sample of 38 (thirty eight) interviewees’ narratives, 20 (twenty) being female and 18 (eighteen) male. Bibliographical, documentary and empirical sources were consulted, however the dialogue between theoretical references and empirical data was a priority. The data showed indicators of the material and social conditions from which youngsters experience their youth condition; also, showed a school context marked by scenes of vigilance, constraints, invisibilities, prejudices and repressions, permeated by the conservative ideology and moralizing bias. The research results demonstrated that IFS school daily life is crossed by the dialectical movement in which brands of disciplinary power are present and (re) produce identities, corporalities, sexualities and youth experiences that are sometimes undermined, silenced, invisible in school and, at the same time, (re) produce resistance from youth identities, who often break with gender roles, the sexist logic of professions, subvert gender regulations, binary prescriptions and investments for the construction of "docile bodies", directly or indirectly related to patriarchal, capitalist and heterosexist regimes.________________________________________________________________________________________________________________________________